Communicating affection : interpersonal behavior and social context - Floyd, Kory (Advances in personal relationships (Cambridge, England), 2006)
"This text explores the scientific research on affection exchange to emerge from the disciplines of communication, social psychology, family studies, psychophysiology, anthropology, and nursing. Specific foci include the individual and relational benefits (including health benefits) of affectionate behavior, as well as the significant risks often associated with expressing affection. A new, comprehensive theory of human affection exchange is offered, and its merits relative to existing theories are explored."--Jacket